1998
DOI: 10.1016/s0377-1237(17)30502-6
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Estimation of Blood Glucose : A Comparative Evaluation

Abstract: Glucose in blood is the most frequent analyzed parameter in a clinical chemistry laboratory. In Armed Forces Laboratories, copper reduction method (Modified Folin Wu) is commonly used. Here we have compared this method as well as O-Toluidine and GOD-POD method with reference UV-Hexokinase method. Both Modified Folin Wu and O-Toluidine showed upward deviation with substantial imprecision (CV=4.9% - 3.5% and 6% - 5.8% respectively) and inaccuracy (Average deviation = 5.76% and 10.68% respectively). GOD-POD metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…19 An automated KONELAB 3i analyzer (Thermofisher Scientific, Waltham, MA, USA) with the GOD-POD and Hexokinase method as per the instructions given with the kits (Thermofisher Scientific, Waltham, MA, USA) were used to estimate blood glucose levels. 20 Briefly, serum samples were mixed with the kit's colorimetric substrate and horseradish peroxidase (Thermofisher Scientific, Waltham, MA, USA) and the reaction was initiated by addition of glucose oxidase (Sigma-Aldrich, St. Louis, Missouri, USA). The microplate was incubated at room temperature for 30 minutes.…”
Section: Determination Of Blood Glucose Levelsmentioning
confidence: 99%
“…19 An automated KONELAB 3i analyzer (Thermofisher Scientific, Waltham, MA, USA) with the GOD-POD and Hexokinase method as per the instructions given with the kits (Thermofisher Scientific, Waltham, MA, USA) were used to estimate blood glucose levels. 20 Briefly, serum samples were mixed with the kit's colorimetric substrate and horseradish peroxidase (Thermofisher Scientific, Waltham, MA, USA) and the reaction was initiated by addition of glucose oxidase (Sigma-Aldrich, St. Louis, Missouri, USA). The microplate was incubated at room temperature for 30 minutes.…”
Section: Determination Of Blood Glucose Levelsmentioning
confidence: 99%
“…The obtained results indicated a trend of improvement in total cholesterol and LDL-C levels in the control group compared to the intervention one, which could be attributed to better compliance of the participants with the given diet and physical activities in the control group. Some of the studies in this regard have shown that the prescription of medication would lead to less consideration of pharmacological recommendations among the patients [17] . As lifestyle modification was applied in both groups, it was to some extent expectable to achieve such results, since the use of this approach for controlling the daily calorie intake is considered as a gold standard of care for the patients with NAFLD [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The solid residue was discarded and a filtrate of the sample was centrifuged at 5,000 rpm for 5 min. The glucose concentration was determined by GOD–POD method . The percentage of cellulose hydrolysis was calculated by using Equation : %0.5emCellulose hydrolysis=Glucose concentration after enzymatic hydrolysis×100Cellulose before enzymatic hydrolysis×1.11 …”
Section: Methodsmentioning
confidence: 99%
“…The glucose concentration was determined by GOD-POD method. 21 The percentage of cellulose hydrolysis was calculated by using Equation (2):…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%